Analisis Entomologi Nyamuk Aedes aegypti dan Aedes albopictus Terhadap Lonjakan Kasus DBD Serta Upaya Penanggulangannya (Studi Kasus di Kecamatan Rengel Tahun 2019-2024) - Toha, Dwiki Muhandisya Arif (Jurnal Riset Kesehatan Masyarakat, 2025)
ENTOMOLOGICAL ANALYSIS OF AEDES AEGYPTI AND AEDES ALBOPICTUS MOSQUITOES ON THE SPIKE IN DENGINEERING CASES AND COMBAT EFFORTS (CASE STUDY IN RENGEL DISTRICT 2019-2024)xv + 55 pages + 8 tables + 10 pictures + 8 attachments Demam Berdarah Dengue (DBD) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti and Aedes albopictus mosquitoes as the main vectors. This study aims to analyze the spike in cases that occurred significantly in Rengel District, Tuban Regency, East Java, in 2024, after the previous five years showed a low and stable trend of cases. The spike in cases reached 36 people, almost double the previous years, with the majority of cases occurring in January to April, which coincides with the rainy season. Entomological factors, such as mosquito habitats that are in accordance with the local environment, climatic factors such as temperatures between 25–30°C, high humidity, and erratic rainfall accelerate the life cycle of mosquitoes and replication of the dengue virus in the vector's body. The results of the analysis show that the 0–15 age group is the most vulnerable group (51.7%) and males are more infected (61%) than females. Karangtinoto Village recorded the highest number of cases, while Ngadirejo Village recorded the lowest. Seasonal patterns and irregular rainfall due to global climate phenomena such as La Niña contribute to the increased risk of transmission. In addition, the decreased effectiveness of control programs such as fogging and mosquito nest eradication, as well as the lack of public awareness in maintaining environmental cleanliness are serious challenges. Therefore, a more intensive and integrated vector control strategy is needed by considering the bioecological aspects of vectors, local environmental conditions, and public education. This study is expected to provide a scientific basis for policy makers in designing more effective vector-based disease risk mitigation measures, especially in the Rengel District and its surroundings.